Performance Enhancement of Dual-Input Frequency-Periodic Load Modulated Power Amplifier at 1–5.7-GHz Bandwidth With Co-Designed Biasing Network - Takuma Torii; Yuji Komatsuzaki; Shintaro Shinjo; Ryo Ishikawa (IEEE Access)
This study proposes a novel dual input power amplifier (PA) with a frequency-periodic load modulated output matching network supported by a broadband biasing network. The output matching network consists of two transmission lines which enable the dual-input PA to operate in Doherty or outphasing modes depending on the frequency. The proposed broadband biasing network simply consists of a short stub circuit that cooperates with the output matching network. The biasing network not only provides a bias to PA, but also improves the bandwidth in the back-off operation over the broadband characteristic of 145%. The two independent input signals are utilized to optimize the operation of Doherty and outphasing mode. The dual-input PA is implemented using a $0.15~μ $ m GaN HEMT process. The fabricated PA shows a saturated output power of 35.2 dBm to 38.1 dBm with a power added efficiency (PAE) of 36.6% to 62% for the broadband 1 GHz to 5.7 GHz. The fabricated PA demonstrated an averaged output power of 27.7 dBm to 31.8 dBm, a PAE of 35% to 56.2% and an adjacent channel power Ratio (ACPR) of -41 to -55 dBc.